The Sanitary Hygiene of Refilled Drinking Water Depots during the Covid-19 Pandemic - Herniwanti Herniwanti; Edi Sudarto; Kamali Zaman; Oktavia Dewi; Novita Rany (Postgraduate, University of Mataram, 2022)
The Coronavirus-19 (Covid-19) pandemic requires people to behave cleanly and healthily to increase the need for clean drinking water. Based on a survey conducted by the Bengkalis District Health Office, it was found that 55% of the people used drinking water from refill depots. The purpose of this study was to determine the Sanitation Hygiene of Drinking Water Depots during the Covid-19 Pandemic in Bengkalis, Riau. This research method is a quantitative descriptive analysis using secondary data from the Bengkalis Health Service for a depot that has sanitation requirements for drinking water depots according to the reference. The research location is in Bengkalis District with a sample of 40 drinking water depots and analyzed for four parameters of drinking water depot sanitation inspection: place, equipment, handlers, and drinking water quality standard certificates. Sanitation hygiene inspection was obtained for the parameters of the place, equipment, and handlers with 100% achievement and only 25% certificate of water quality standard and proper hygiene. It is necessary to innovate drinking water treatment technology for drinking water sources that are healthy, guaranteed, cheap, and free from disease and to support the PHBS and STMB programs during the Covid-19 period.